Nerve conduction velocity is independently associated with bone mineral density in type 2 diabetes mellitus - Chen, Xiao-jing; Wang, Xiao-feng; Pan, Zheng-can; Zhang, Deng; Zhu, Ke-cheng; Jiang, Tao; Kong, Xiao-ke; Xie, Rui; Sun, Li-hao; Tao, Bei; Liu, Jian-min; Zhao, Hong-yan (Frontiers in Endocrinology, 2023)
Aim: This study investigated the association between nerve conduction velocity (NCV) and bone mineral density (BMD) in patients with type 2 diabetes mellitus (T2DM). Methods: This study retrospectively collected medical data of T2DM patients who underwent dual-energy X-ray absorptiometry and nerve conduction study at the Shanghai Ruijin Hospital, Shanghai, China. The primary outcome was the total hip BMD T-score. The main independent variables were motor nerve conduction velocities (MCVs), sensory nerve conduction velocities (SCVs), and composite Z-scores of MCV and SCV. T2DM patients were divided into total hip BMD T-scores < -1 and total hip BMD T-scores ≥ -1 groups. The association between the primary outcome and main independent variables was evaluated by Pearson bivariate correlation and multivariate linear regression. Results: 195 female and 415 male patients with T2DM were identified. In male patients with T2DM, bilateral ulnar, median, and tibial MCVs and bilateral sural SCVs were lower in the total hip BMD T-score < -1 group than T-score ≥ -1 group (P < 0.05). Bilateral ulnar, median, and tibial MCVs, and bilateral sural SCVs showed positive correlations with total hip BMD T-score in male patients with T2DM (P < 0.05). Bilateral ulnar and tibial MCVs, bilateral sural SCVs, and composite MCV SCV and MSCV Z-scores were independently and positively associated with total hip BMD T-score in male patients with T2DM, respectively (P < 0.05). NCV did not show significant correlation with the total hip BMD T-score in female patients with T2DM. Conclusion: NCV showed positive association with total hip BMD in male patients with T2DM. A decline in NCV indicates an elevated risk of low BMD (osteopenia/ osteoporosis) in male patients with T2DM.